Report of Health Week Committee
1924-02-25 1924 1920s 4 pages Report of Health Week Committee one from the Girls' side, selected by the Head Teacher of each School) were received, and 50 prizes of 10s. each in books were awarded. The essays indicated that careful instruction in the essentials of Hygiene and Health Living had been given in the schools, and the Committee expressed their appreciation of the assistance rendered by the teachers. Meetings were arranged at Deptford, St. Pancras, Islington, Holborn, Bromley, Wimbledon, Southgate, and Uxbridge. Valuable assistance was rendered by the League of Nations Union who issued a leaflet on "What the League of Nations has done for the Health of the World," and on "Health : The Workman's Capital." These facts indicate an increasing number of centres taking up the work, and also larger and more comprehensive programmes, and encourage good hopes for the future progress of the movement which has for its object the focussing of public attention on matters of health and the arousing of that sense of personal responsibility for health, without which all public work, whether by the Government or local authorities must fall short of its aims. The dominant idea for this year was "Self Help in Health" and the consideration of what each individual can do for himself and his neighbour in securing a healthy life. The Committee worked in close co-operation with the National Baby Week Council during the year. In some cases, however, it has been found practicable to combine the two, and it is interesting to note that the Astor Shield for the local Baby Week which holds the most effective campaign was last year awarded to West Bromwich, where a combined Baby Week and Health Week was held in October. Filed in the office there are a considerable number of specimen programmes, leaflets, cards and posters, used at different centres. These specimens are most useful and suggestive for reference by those thinking of arranging for Health Week celebrations. The accounts show that donations towards the work were received from the Right Hon. T.R. Ferens, the British Commercial Gas Association, the Chadwick Trust, Kent Insurance Committee, Guardian Assurance Co., Ltd., London and Manchester Assurance Co., Ltd., National Mutual Life Assurance Society, Refuge Assurance Co., Ltd., and the Royal Liver Friendly Society, amounting to £172, and after meeting expenses there is a small balance in hand to carry forward to next year. Health Week Committee, 90, Buckingham Palace Road, S.W.1. 292/842/1/10